ISLAMIC TWISTS AND THE DECLINE OF ISLAMISM IN INDONESIA - Endang Turmudi (Harmoni, 2016)
Islamism or the ideologization of Islam has actually grown and embraced by some Islamic leaders when politics is used as a medium of struggle. Since its inception in late 1945, Islamic political parties and their leaders have placed Islam as party ideology. Despite the incapability of Islamic politics to not accepting the policy of “Azas Tunggal” (sole ideology) as politically set up by the New Order government, the passion of Islamism seems to reappear when the political reforms took place following the fall of Suharto in 1998. An issue to make Indonesia an Islamic State was raised again by the proponents of political Islam through Islamic political party as well as by those who were proponents of transnational Islamic organizations. It is argued that Islamic twists which are marked by the increase in Indonesian Muslim religiosity must be strengthening a tendency of Islamism which develops in society since it is a part of Muslim’s religious piety. However, Islamism seemed to be declining as though it suggests that there is no correlation between the tendency of Islamism and the increase of people’s religious mindedness. Amidst the tendency of Muslims to practice true religion, for example, the Islamic political parties have decreased in its support by Muslims.